2018
DOI: 10.1080/21691401.2018.1458233
|View full text |Cite
|
Sign up to set email alerts
|

The use of chitosan/PLA nano-fibers by emulsion eletrospinning for periodontal tissue engineering

Abstract: The combination of chitosan nano-particles enhanced the mechanical properties of pure PLA nano-fibers and increased its hydrophilicity. Pure PLA nano-fibers scaffold facilitated BMSCs proliferation. Adding an appropriate amount of chitosan nano-particles may promote its properties of cell proliferation and osteogenic differentiation. The higher expression of inflammatory mediators caused by nano-fibers may be regulated via TLR4 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…The literature gives different results concerning the variation of the mechanical properties including impact ones of PLA by plasticization with PEG. Bijarimi et al [105] found that tensile and flexural strength, stiffness and notched Izod impact strength decreased significantly when the PEG at 2.5–10 wt% concentrations were added to the PLA matrix It was found that the PLA/chitosan composite materials showed appropriate porosity and structure, and could keep certain shape and mechanical properties [67]. The processing morphological, structural, thermal and mechanical performance of electrospun biocomposites based on PLA blended with 25 wt% of poly(hydroxybutyrate) (PHB), plasticized with 15 wt% of acetyl(tributyl citrate) (ATBC) and loaded with 1–5 wt% of chitosan or catechin microparticles have been studied by Arrieta et al [106].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature gives different results concerning the variation of the mechanical properties including impact ones of PLA by plasticization with PEG. Bijarimi et al [105] found that tensile and flexural strength, stiffness and notched Izod impact strength decreased significantly when the PEG at 2.5–10 wt% concentrations were added to the PLA matrix It was found that the PLA/chitosan composite materials showed appropriate porosity and structure, and could keep certain shape and mechanical properties [67]. The processing morphological, structural, thermal and mechanical performance of electrospun biocomposites based on PLA blended with 25 wt% of poly(hydroxybutyrate) (PHB), plasticized with 15 wt% of acetyl(tributyl citrate) (ATBC) and loaded with 1–5 wt% of chitosan or catechin microparticles have been studied by Arrieta et al [106].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper [65] it was demonstrated that the rosemary alcoholic extract incorporation into PLA confers good elongation at break, rheological properties, antioxidant and antimicrobial activities, barrier properties and a good biocompatibility. A number of studies have been carried out on physical, mechanical, and morphological properties evaluation of PLA/CS system [65,66,67,68,69]. These systems show good antimicrobial properties but they have inferior flexibility and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments have also shown excellent bone induction. 22,23 Nanoparticles are considered as favorable analogs of human microstructure and were proven to have excellent tissue regeneration effects in the present study. Periodontitis tends to recur; however, the recurrence rate of periodontitis may be decreased through implanting drugs that can resist bacteria for a long period in the periodontal pocket.…”
Section: Discussionmentioning
confidence: 95%
“…But it lacks mechanical stability and solubility in water, and leads to the brittle nature of scaffolds. It can be blended with different synthetic polymers, like PLA (Shen et al, 2018), PCL (Masoudi et al, 2017), and bioceramics, etc. to make up for these shortcomings.…”
Section: Nano-composite Electrospun Fibers In Periodontal Regenerationmentioning
confidence: 99%
“…In addition, PLA is poor in hydrophilic property (Li et al, 2006). To overcome these disadvantages, Shen et al (2018) embedded chitosan, the natural alkaline polymer, with PLA by electrospinning approach to improve its hydrophilicity and reduce acid products.…”
Section: Nano-composite Electrospun Fibers In Periodontal Regenerationmentioning
confidence: 99%